Individual risk factors and prediction of gambling disorder in online sports bettors - the longitudinal RIGAB study - Wirkus, Theresa; Czernecka, Robert; Bühringer, Gerhard; Kräplin, Anja (Frontiers in Psychiatry, 2024)
While research in online sports betting is dominated by studies using objective player tracking data from providers to identify risky gambling behavior, basic research has identified various putative individual risk factors assumed to underlie the development of gambling disorder across all types of gambling. This study aims to examine individual risk factors and their longitudinal clinical relevance in online sports bettors. German online sports bettors (N = 607, Mage = 34, 92% male) from a provider based sample took part in an online survey. The study team randomly preselected customers to be invited. N = 325 (53,45%) of the participants also took part in an online follow-up survey one year later. Cross-sectional and longitudinal associations of putative risk factors and DSM-5 gambling disorder in online sports bettors were analyzed. These risk factors include alcohol and tobacco use, impulsivity, difficulties in emotion identification, emotion regulation strategies, comorbid mental disorders and stress. We found more pronounced impulsivity, difficulties in emotion identification, emotion suppression, comorbid mental disorders and stress were cross-sectionally associated with gambling disorder, and longitudinally predicted gambling disorder in online sports bettors (with the exception of emotion suppression). In an overall model only lack of premeditation and perceived helplessness remained significant as predictors for gambling disorder. Online sports bettors with gambling disorder predominantly showed more pronounced risk factors, which were also confirmed longitudinally as relevant for the maintenance of gambling disorder. Risk factors such as impulsivity and stress and appropriate coping mechanisms should consequently be integrated not only into prevention efforts to identify individuals at risk early, but also into intervention efforts to tailor treatment.